A contribution for thermoeconomic modelling: A methodology proposal - Silveira, Jose Luz [UNESP]; Tuna, Celso Eduardo [UNESP]; Lamas, Wendell de Queiroz; de Castro Villela, Iraides Aparecida (Pergamon-Elsevier B.V. Ltd, 2010)
This work presents a thermoeconomic optimization methodology for the analysis and design of energy systems. This methodology involves economic aspects related to the exergy conception, in order to develop a tool to assist the equipment selection, operation mode choice as well as to optimize the thermal plants design. It also presents the concepts related to exergy in a general scope and in thermoeconomics which combines the thermal sciences principles (thermodynamics, heat transfer, and fluid mechanics) and the economic engineering in order to rationalize energy systems investment decisions, development and operation. Even in this paper, it develops a thermoeconomic methodology through the use of a simple mathematical model, involving thermodynamics parameters and costs evaluation, also defining the objective function as the exergetic production cost. The optimization problem evaluation is developed for two energy systems. First is applied to a steam compression refrigeration system and then to a cogeneration system using backpressure steam turbine. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Exergy; Optimization; Thermal systems; Thermoeconomics